2004
DOI: 10.1046/j.0022-202x.2003.22108.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α and Interferon-γ Polymorphisms Contribute to Susceptibility to Oral Lichen Planus

Abstract: Most lymphocytes in the lamina propria of oral lichen planus (OLP) lesions express and secrete interferon-gamma (IFN-gamma) and tumor necrosis factor-alpha (TNF-alpha), whereas they do not secret interleukin-4 and -10 or transforming growth factor-beta. We analyzed whether the polymorphisms of several cytokines may influence the susceptibility to OLP. Cytokine typing was performed by a sequence-specific PCR assay. Thirteen cytokine genes with 22 single-nucleotide polymorphisms were studied. IFN-gamma UTR 5644 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
126
2
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(150 citation statements)
references
References 45 publications
10
126
2
3
Order By: Relevance
“…Carrozzo et al investigated the polymorphism of IFN-γ and TNF-α using polymerase chain reaction (PCR) in 44 cases with LP and reported that these cytokines influence the clinical type of the disease and contribute to the predisposition to LP, and they stressed that their results contradicted those of previous studies [30]. Yamamoto et al evaluated the serum IFN-γ levels of 30 patients diagnosed with OLP by enzyme immunoassay method and found serum IFN-γ production to be slightly lower than in the control group.…”
Section: Discussioncontrasting
confidence: 49%
“…Carrozzo et al investigated the polymorphism of IFN-γ and TNF-α using polymerase chain reaction (PCR) in 44 cases with LP and reported that these cytokines influence the clinical type of the disease and contribute to the predisposition to LP, and they stressed that their results contradicted those of previous studies [30]. Yamamoto et al evaluated the serum IFN-γ levels of 30 patients diagnosed with OLP by enzyme immunoassay method and found serum IFN-γ production to be slightly lower than in the control group.…”
Section: Discussioncontrasting
confidence: 49%
“…Indeed, cutaneous idiopathic LP is frequently associated with the HLA-DR1 allele, whereas idiopathic OLP is not [9]. However, a linkage disequilibrium of the -308A TNF-α promoter polymorphism with HLA-DR3 has reported in Caucasians [10]. Recently, the gene for cytotoxic T lymphocyte antigen 4 (CTLA-4) has been identified, able to confer the susceptibility to HT [6].…”
Section: Discussionmentioning
confidence: 99%
“…The significantly increased frequencies of the UTR 5644T allele and AT and TT genotypes in our GO patients are in support of the hypothesis. This polymorphism is involved in pathogenesis of Behcet's disease 36 and lichen planus, 37 but to our knowledge this study is the first to suggest the involvement of this polymorphism in GO.…”
Section: Discussionmentioning
confidence: 90%